National Data of CPR Procedures Performed on Hospitalized Thai Older Population Patients - Panita Limpawattana (2018)
© 2015, Taiwan Society of Geriatric Emergency and Critical Care Medicine. Published by Elsevier Taiwan LLC. All rights reserved. Background Little is known about the epidemiology of the elderly who receive cardiopulmonary resuscitation (CPR) and the subsequent survival factors in Thailand and other developing countries. The objective of this study was to determine the rate of CPR and the survival rate among hospitalized Thai elderly patients, and also factors predicting survival at discharge. Methods National databases from three sources were searched. These three systems accounted for 96% of the Thai population. All inpatients in the fiscal year 2010 (from October 1, 2009 to September 31, 2010) aged 60 years or over who received CPR procedure were included. Baseline characteristics were studied. The study outcomes were CPR rate, mortality rate, and survival factors. Results In total, 17,813 elderly patients who were hospitalized during the 2010 fiscal year received CPR (997.2/100,000 older adults). Of those, 5125 patients (28.77%) survived at discharge. Pre-existing comorbidity, asystole, time on a mechanical ventilator > 96 hours, and being admitted to a private hospital were associated with poorer outcomes (p < 0.05). Conclusion The rate of CPR in hospitalized elderly patients was 997.2 events/100,000 older adults with a survival rate of 28.77%. Factors predicting death at discharge are pre-existing comorbidities, cardiac arrhythmia type, intervention/procedure, and type of hospital.